Kajian Teks-Teks Melayu Islam di Barat: Masalah Dan Kesalahfahaman Utama - Denisova, Tatiana (Afkar: Jurnal Akidah dan Pemikiran Islam, 2008)
The global conflict between Western and Muslim world causes the spread of some mithos and misunderstanding regarding Early Muslim History in Malay World and the influence of Islam in Malay history and culture. Till now these questions are subject of scientific and political discussion. The Malay Muslim historical chronicles contain a lot of information and references about the history of the Islamization in Malay world: when it was begun, who brought the â€˜new religionâ€ to the Malay Archipelago and who spread Islam here; where Islam came from etc. The study of all these texts as historical sources helps to discover many of these important questions.